S‐Block Metal Mg‐Mediated Co─N─C as Efficient Oxygen Electrocatalyst for Durable and Temperature‐Adapted Zn–Air Batteries - Henan Wang; Xinxin Niu; Wenxian Liu; Ruilian Yin; Jiale Dai; Wei Guo; Chao Kong; Lu Ma; Xia Ding; Fangfang Wu; Wenhui Shi; Tianqi Deng; et al. (Advanced Science)
Abstract In the quest to enhance Zn–air batteries (ZABs) for operating across a wide spectrum of temperatures, synthesizing robust oxygen electrocatalysts is paramount. Conventional strategies focusing on orbital hybridization of d–d and p‐d aim to moderate the excessive interaction between the d‐band of the transition metal active site and oxygen intermediate, yet often yield suboptimal performance. Herein, an innovative s‐block metal modulation is reported to refine the electronic structure and catalytic behavior of Co─NC catalysts. Employing density functional theory (DFT) calculations, it is revealed that incorporating Mg markedly depresses the d‐band center of Co sites, thereby fine‐tuning the adsorption energy of the oxygen reduction reaction (ORR) intermediate. Consequently, the Mg‐modified Co─NC catalyst (MgCo─NC) unveils remarkable intrinsic ORR activity with a significantly reduced activation energy (Ea) of 10.0 kJ mol−1, outstripping the performance of both Co─NC (17.6 kJ mol−1), benchmark Pt/C (15.9 kJ mol−1), and many recent reports. Moreover, ZABs outfitted with the finely tuned Mg0.1Co0.9─NC realize a formidable power density of 157.0 mW cm−2, paired with an extremely long cycle life of 1700 h, and an exceptionally minimal voltage gap decay rate of 0.006 mV h−1. Further, the Mg0.1Co0.9─NC‐based flexible ZAB presents a mere 2% specific capacity degradation when the temperature fluctuates from 25 to −20 °C, underscoring its robustness and suitability for practical deployment in diverse environmental conditions.